A “looming bias” in spatial hearing? Effects of acoustic intensity and spectrum on categorical sound source localization - McCarthy, Lisa; Olsen, Kirk N. (Attention, perception & psychophysics, 2017)
Continuous increases of acoustic intensity ( up - ramps ) can indicate a looming (approaching) sound source in the environment, whereas continuous decreases of intensity ( down - ramps ) can indicate a receding sound source. From psychoacoustic experiments, an “adaptive perceptual bias” for up-ramp looming tonal stimuli has been proposed (Neuhoff, 1998 ). This theory postulates that (1) up-ramps are perceptually salient because of their association with looming and potentially threatening stimuli in the environment; (2) tonal stimuli are perceptually salient because of an association with single and potentially threatening biological sound sources in the environment, relative to white noise, which is more likely to arise from dispersed signals and nonthreatening/nonbiological sources (wind/ocean). In the present study, we extrapolated the “adaptive perceptual bias” theory and investigated its assumptions by measuring sound source localization in response to acoustic stimuli presented in azimuth to imply looming, stationary, and receding motion in depth. Participants ( N = 26) heard three directions of intensity change (up-ramps, down-ramps, and steady state, associated with looming, receding, and stationary motion, respectively) and three levels of acoustic spectrum (a 1-kHz pure tone, the tonal vowel /ә/, and white noise) in a within-subjects design. We first hypothesized that if up-ramps are “perceptually salient” and capable of eliciting adaptive responses, then they would be localized faster and more accurately than down-ramps. This hypothesis was supported. However, the results did not support the second hypothesis. Rather, the white-noise and vowel conditions were localized faster and more accurately than the pure-tone conditions. These results are discussed in the context of auditory and visual theories of motion perception, auditory attentional capture, and the spectral causes of spatial ambiguity.